Tax systems, tax revenue and growth in LDCs: A review of empirical evidence - Norman Gemmell (Intereconomics, 1988)
The relationship between taxation, savings and growth is a complex one, which economists to date have only partially been able to explain. The following paper reviews empirical evidence on differences in tax systems and their operation between developed and less developed countries and the role of various taxes in the development process, and examines some evidence on the effects of taxation on economic growth in LDCs.
Keywords: 330; Development Strategy